2022
DOI: 10.1177/09589287221085922
|View full text |Cite
|
Sign up to set email alerts
|

The welfare state in really hard times: Political trust and satisfaction with the German healthcare system during the COVID-19 pandemic

Abstract: The COVID-19 pandemic represents an enormous challenge for healthcare systems around the globe. Using original panel survey data for the case of Germany, this article studies how specific trust in the healthcare system to cope with this crisis has evolved during the course of the pandemic and whether this specific form of trust is associated with general political trust. The article finds strong evidence for a positive and robust association between generalized political trust and performance perceptions regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
(62 reference statements)
0
11
0
2
Order By: Relevance
“…Furthermore, confidence in the court system seems to be a predisposition for agreeing with judicial reasoning. This is particularly relevant against the backdrop of the extensive and ongoing research on the role of trust in institutions during the COVID-19 pandemic (Busemeyer, 2022;Erhardt et al, 2021;Toshkov et al, 2022;Zaki et al, 2022). Shirazi et al (2024) apply the perspective of the Multiple Streams Framework (MSF, DeLeo et al, 2024;Herweg et al, 2023) that is well established in international policy research to a national context that has been little studied here.…”
Section: Cultural Biases Agenda Setting and The Regulation Of Policy ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, confidence in the court system seems to be a predisposition for agreeing with judicial reasoning. This is particularly relevant against the backdrop of the extensive and ongoing research on the role of trust in institutions during the COVID-19 pandemic (Busemeyer, 2022;Erhardt et al, 2021;Toshkov et al, 2022;Zaki et al, 2022). Shirazi et al (2024) apply the perspective of the Multiple Streams Framework (MSF, DeLeo et al, 2024;Herweg et al, 2023) that is well established in international policy research to a national context that has been little studied here.…”
Section: Cultural Biases Agenda Setting and The Regulation Of Policy ...mentioning
confidence: 99%
“…Furthermore, confidence in the court system seems to be a predisposition for agreeing with judicial reasoning. This is particularly relevant against the backdrop of the extensive and ongoing research on the role of trust in institutions during the COVID‐19 pandemic (Busemeyer, 2022; Erhardt et al., 2021; Toshkov et al., 2022; Zaki et al., 2022).…”
mentioning
confidence: 99%
“…In terms of the relation between the equivalent framing effect and citizen satisfaction in the context of low government trust, Du et al (2022) found that under a negative framework, citizens with low trust in the government may be reminded of their powerlessness and lack of resources, rendering them less inclined to act. This may mean that in the satisfaction evaluation, the trust of these citizens in the government is so much less (Busemeyer, 2022) that there is no room for negative bias, even though some studies have reported negative bias in the satisfaction evaluation (Cantarelli et al, 2020;Olsen, 2015). When citizens distrust or lose confidence in the government, the manipulation of performance information presentation may not be conducive to the improvement of citizen satisfaction.…”
Section: Trust In Government and Equivalent Framing Effect Of Citizen...mentioning
confidence: 99%
“…Since early 2020, the coronavirus disease 2019 (COVID-19) pandemic has posed major challenges to the German health care system both on structural and individual level [1][2][3][4][5]. In particular, intensive care units (ICU) have been severely impacted during periods of increased COVID-19 caseloads with a total daily occupancy of more than 5,000 adult COVID-19 patients distributed across approximately 1,300 adult ICU nationwide [6].…”
Section: Introductionmentioning
confidence: 99%